Research on multi-objective grid task scheduling algorithms based on survivability and Makespan - WANG Shu-peng; YUN Xiao-chun; YU Xiang-zhan (Tongxin Xuebao, 2006)
In the complex and dynamic Grid system,failure of resources was very common.And the failure of Grid re-sources can halt the execution of tasks on them.To mitigate this problem,the concept of tasks survivability was pro-posed,a local objective function which can be adjusted was proposed by incorporating the makespan and survivability of tasks and maximizing the survivability of tasks was devised.The simulation results confirm that the scheduling algorithm can trade off these two objectives,and can satisfy different demand by adjusting the weight parameter in the objective function.So it can be applied in the complex Grid computing environment well.